Opinion: Let's make sidewalk cycling a thing of the past - Waters, Christopher (The Windsor Star, 2017)
A historical and evidence-based perspective, however, suggests that sidewalk riding is a sideshow to bigger issues of safety for all road users.
Keywords: Christopher Waters